2015
DOI: 10.1007/978-3-319-24932-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Radiation Therapy (PRT) for Lung Cancer

Abstract: This chapter reviews and discusses approaches and strategies of personalized radiation therapy (PRT) for lung cancers at four different levels: (1) clinically established PRT based on a patient's histology, stage, tumor volume and tumor locations; (2) personalized adaptive radiation therapy (RT) based on image response during treatment; (3) PRT based on biomarkers; (4) personalized fractionation schedule. The current RT practice for lung cancer is partially individualized according to tumor histology, stage, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…This difference may be because metastatic breast cancer is more sensitive to endocrine therapy, chemotherapy or molecularly targeted drug therapy . The survival analysis indicated that radiation only had a beneficial effect for those with metastases from lung cancer, and radiation is one of the main treatment methods for lung cancer . However, radiation may deteriorate the condition of skin cancer, which is not sensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be because metastatic breast cancer is more sensitive to endocrine therapy, chemotherapy or molecularly targeted drug therapy . The survival analysis indicated that radiation only had a beneficial effect for those with metastases from lung cancer, and radiation is one of the main treatment methods for lung cancer . However, radiation may deteriorate the condition of skin cancer, which is not sensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics, as a non-invasive, quantitative, and low-cost approach, can objectively and comprehensively evaluate tumor heterogeneity by converting medical images into high-dimensional, mineable, and quantitative imaging features via high-throughput extraction of data-characterization algorithms (Aerts et al, 2014 ; Gillies et al, 2016 ). These features can reveal disease progression, providing valuable information for personalized therapy and decision-support (Chicklore et al, 2013 ; Cameron et al, 2016 ; Huynh et al, 2016 ; Jin and Kong, 2016 ; Kotrotsou et al, 2016 ; Parekh and Jacobs, 2016 ; Ginsburg et al, 2017 ; Lee et al, 2017 ; Marin et al, 2017 ; Scalco and Rizzo, 2017 ; Shafiq-Ul-Hassan et al, 2017 ). Previous studies have shown that the radiomics signature alone or merged with clinical parameters could enhance predictive accuracy in cancers (Huang Y. et al, 2016 ; Huang Y. Q. et al, 2016 ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, a noninvasive, quantitative, and low-cost approach, can objectively and comprehensively evaluate tumor heterogeneity by converting medical images into high-dimensional, mineable, and quantitative imaging features via high-throughput extraction of data-characterization algorithms [11,12]. These features have potential to reveal disease progression, thereby provide valuable information for personalized therapy and decision-support [13][14][15][16][17][18][19][20][21][22][23]. Previous studies have shown radiomics signature alone or merged with clinical parameters could enhance predictive accuracy in cancers [24][25][26].…”
Section: Introductionmentioning
confidence: 99%